Isolation and Pathogenic Characterization of Vibrio bivalvicida Associated With a Massive Larval Mortality Event in a Commercial Hatchery of Scallop Argopecten purpuratus in Chile - Rojas, Rodrigo; Miranda, Claudio D.; Romero, Jaime; Barja, Juan L.; Dubert, Javier (Frontiers in Microbiology, 2019)
The VPAP30 strain was isolated as the highly predominant bacteria from an episode of massive larval mortality occurring in a commercial culture of the Chilean scallop Argopecten purpuratus. The main aims of this study were, to characterize and identify the pathogenic strain using biochemical and molecular methods, to demonstrate its pathogenic activity on scallop larvae, to characterize its pathogenic properties and to describe the chronology of the pathology. The pathogenic strain was identified as Vibrio bivalvicida based on its phenotypic properties, the multilocus sequence analysis of eight housekeeping genes (ftsZ, gapA, gyrB, mreB, pyrH, recA, rpoA and topA) and different in silico genome-to-genome comparisons. When triplicate cultures of healthy 10–day–old scallop larvae were challenged with 1×105 colony forming units (CFU) mL-1 of the VPAP30 strain, percentages of larval survival of 78.9 ± 3.3%, 34.3 ± 4.9% and 0% were observed at 12, 24 and 36 h, respectively; whereas uninfected larval cultures showed survival rates of 97.4 ± 1.2% after of 48 h. Infected scallop larvae showed accumulation of bacteria around the larvae, velum disruption and necrosis of digestive gland. The 50% lethal dose (LD50) of VPAP30 strain at 24 and 48 h was 1.3×104 and 1.2×103 CFU mL-1, respectively. 5-DTAF staining was used to reveal the invasive activity of the VPAP30; a complete bacterial dissemination inside the larvae at 24 h post-infection was observed. Larvae treated with cell-free extracellular products (ECPs) of VPAP30, showed survival rate of 59.5 ± 1.7%, significantly (P<0.001) lower than the control group (97.4 ± 1.2%) whereas larvae treated with heat-treated ECPs exhibited a survival rate of 61.6 ± 1.8% after 48 h. V. bivalvicida VPAP30 exhibits high pathogenic activity on scallop larvae, mediated both by bacterial invasion and the production of toxigenic heat-stable compounds. This report constitutes the first isolation of V. bivalvicida out of Europe and extends the host range of this species, having demonstrated its pathogenic activity on the A. purpuratus. These results supporting the pathogenic potential of V. bivalvicida to kill the larvae of a broad range of bivalve species reared in hatcheries located in the Atlantic and the Pacific coasts.